The impact of pair programming on students logical thinking : a case study on higher academic institution / Mahfudzah Othman … [et al.] - Othman, Mahfudzah; Rosmani, Arifah Fasha; Mohd Fauzi, Shukor Sanim; Mazlan, Umi Hanim (Penerbit UiTM (UiTM Press), 2019)
Pair Programming (PP) is a well-known agile software development technique that has been widely implemented in programming classes. Through PP, students are able to share knowledge and expertise that will contribute to better programming solutions. Nevertheless, how PP can help to improve students’ cognitive abilities has yet to be explored. Therefore, this study’s aim was to investigate the impacts of implementing Pair Programming (PP) on students’ logical thinking. Logical thinking is part of the cognitive ability claimed to be one of the crucial factors that determine the success or failure of novice programmers. To achieve this, 60 students who enrolled in Diploma in Computer Science programme in Universiti Teknologi MARA Perlis Branch, Malaysia, were asked to take the pre-test and post-test of Group Assessment Logical Thinking (GALT) Test in the beginning and at the end of the semester. These students were divided into two main groups; Control and Test in the Test Group, students with low logical ability will be paired with their high logical thinking friends. Meanwhile, in the Control Group, no pair programming or collaborative technique took place. Five programming tasks were assigned to both groups to solve either collaboratively or individually. The results obtained via paired sample t-tests statistical analysis shows significant improvements in students’ logical thinking with p-value <0.05 in the Test Group